The Implementation of Iron Supplementation and Antenatal Counseling for Iron Deficiency Anemia in Pregnancy - Darmawati, Darmawati; Tahlil, Teuku; Siregar, Toungku Nizwan; Kamil, Hajjul; Audina, Masyithah (Jurusan Keperawatan FIKES UNSOED, 2019)
Anemia is one of the contributing conditions that cause maternal mortality in Indonesia. The Indonesian Ministry of Health try to reduce it through an antenatal care program conducted at public health center, with several indicators including iron supplementation and antenatal counseling. This study was conducted to find out the relationship between iron supplementation and antenatal counseling to iron deficiency anemia during pregnancy. This study was a correlative study with cross sectional approach carried out in February until June 2018. The population was 1,285 pregnant women with 102 samples recruited using purposive sampling technique. Blood hemoglobin levels were examined using Hb Meter. Data collection were carried out through guided interviews. Data analysis was done using Chi-Square Test. The implementation of iron supplementation and antenatal counseling was implemented comprehensively (51.0%; 64.7% respectively). This study showed that there was a relationship between iron supplementation and iron deficiency anemia (0.000) and there was no relationship between antenatal counseling and iron deficiency anemia (0.249). It is recommended to all antenatal providers to improve the service provided, especially the iron supplementation that accompanied by giving information through antenatal counseling, so the high maternal mortality rates due to iron deficiency anemia can be treated immediately.